СТРАТИГРАФИ БА ТЕКТОНИКИЙН ЗАРИМ НЭР ТОМЪЁО, НЭГЖҮҮДИЙГ ХЭРЭГЛЭХ ТУХАЙ - Ж.БЯМБА; Н.МӨНХБИЛЭГ (Geological Issues, 2023)
The definitions of terms relating to heat raises the broader issue of the nature of scientific terms and their role in instruction. Some writers, speakers, and students have problems with clear usage of tectonic and stratigraphic terminology. The basic categories of tectonic and stratigraphic units are: 1) material; 2) nonmaterial: 3) hybrid. Both formal and informal tectonic and stratigraphic units are recognized. In illustrations of tectonic and stratigraphic units, it is important to distinguish clearly between scales of time, position and geological features. Geological bodies and units are not measured in years, or time in meters!